SISTEM INFORMASI PELAYANAN IMUNISASI BALITA PADA RSIA(rumah sakit ibu dan anak) BUAH HATI PAMULANG BERBASIS WEB - Akbar Maghriba, - (2018)
This research is to facilitate the running system on immunization at Maternal and Child Hospital Buah Hati Pamulang. This immunization information system is designed for hospital and immunization patients at Maternal and Child Hospital Buah Hati Pamulang. This application is to provide information on immunization, pediatric practice schedule, immunization scheduling, medical record immunization, and web-bassed immunization reminder. Immunization application can be accessed anywhere and anytime without spending time for coming to the hospital to seek information immunization. The hospital will also remind the mother to immunize based on the immunization patient's schedule by sending a message using SMS Gateway. In the proposed system, the author uses PHP and MySql as the database programming language. The information system designed to facilitate the immunization process that runs on Buah Hati Hospital and reminds the mother of the importance of immunization for their toddlers. That way, will reduce mortality or disability in toddlers